ASPEK HUKUM KREDIT BERMASALAH DI PT. BANK INTERNATIONAL INDONESIA CABANG SURABAYA - Susatyo, Rakhmad (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2011)
Banking was one of fund resource for both individual and corporation in order to fulfill need of fund. In giving the credit banking will be carefully and through deep analysis. But in giving their credit some times credit given by the debtor not back on time. This condition called credit problem. That credit problem annoyed bank performance, therefore credit problem should be solved by both litigation or non litigation line. PT. Bank International IndonesiaSurabaya Branch Office as research located of this tesis to choose credit problem by non litigation line. This research uses a normative juridical approach method, which is a research that uses the legal norms which are explained to those ways of researching and discussing the legal regulations in effect at this time. More emphasis on the normativeÂ study of the legislation concerning the settlement of problem loan for banking.Key word : credit, litigation, non litigation